THE ASYMMETRIC EFFECTS OF CURRENCY DEVALUATION IN SELECTED SUB-SAHARAN AFRICA - Chukwudi Odionye, Joseph; Okechukwu Chukwu, Jude (Economic Annals, 2021)
Economic activities in many sub-Saharan African (SSA) countries have weakened markedly in the last few years, with deterioration in trade balances, increasing foreign reserve depletion, and exchange rate depreciation. This situation has led to a call by the International Monetary Fund for more flexible exchange rate adjustment and even currency devaluation to reverse the economic downturn. This call for devaluation has generated controversy among economists and policymakers in these countries and has revived the need to study the effects of devaluation on economic output in SSA countries. This study therefore examines the asymmetric effects of currency devaluation as a policy shift on economic output between 1980 and 2019 in six selected SSA countries, namely Ghana, Kenya, Tanzania, Mozambique, Nigeria, and Malawi. The study employs the smooth transition regression (STR) model to determine the relative asymmetric responses of economic output to devaluation and nondevaluation regimes. The results of STR are mixed, as devaluation asymmetrically impacts positively and significantly on economic output in Ghana, Kenya, Tanzania, and Mozambique, but is insignificant in the case of Nigeria and Malawi. This mixed result suggests that the impact of currency devaluation on economic output differs across countries depending on the structure and size of the economy, the nature of goods produced, and the supportive policies in place, among other things. The policy implication of the findings is that policymakers in various countries should understand the peculiarity of core macroeconomic variables in order to design and implement robust policies.